Activity Assay of Etanol Ectract of Lansau As Antihyperlipidemic - Ruslin Ruslin; Henny Kasmawati; Suriani Suriani; Sundar Ihsan; Desi Sartina (Indonesian Journal of Pharmaceutical Science and Technology, 2019)
Hyperlipidemia is a condition due to increased levels of total cholesterol such as triglycerides, Low Density Lipoprotein (LDL) and decreased levels of High Density Lipoprotein (HDL). Hyperlipidemia can trigger wall thickening and narrowing of arteries, this condition can cause abnormality of fat metabolism in the blood and creates chronic disease. Lansau herb of the Muna tribe of Southeast Sulawesi consists of 44 ingredients of medicinal plants empirically used to treat various diseases such as koleseterol. The aim of this study was to determine the effect of ethanolic extract to the hispatology of the liver that had hyperlipidemia. The parameters are fatty cell and necrosis forming. Mice were induced by cholesterol and high-fat feed. 24 wistar rats were divided into 6 groups consisting of normal control (1% Na CMC), cholesterol and high fat diet food induction control, positive control (simvastatin 0.4 mg / kgbw), group 1 (dose 6.907 mg / kgbw) group II (dose 13.814 mg /kgbw), group III (dose 27.628 mg/kgbw). After 14 days of treatment, hispatological datas  of liver were observed. The results showed that the ethanol extract of lansau had the potential activity as antihyperlipidemia, and cell repairing, especially in administering doses of 27.628 mg/kgbw and had effectiveness that was not much different from the administration of simvastatin in reducing fat degeneration and cell death.Key word : Aterosclerosis, hyperlipidemic, Lansau, simvastatin.